Tell it to the King - King, L., Occhiogrosso, P. (New York G. P. Putnams Sons, 1988)
It is true tales and tall stories from the king of late-night radio and television. In his 30 years of broadcasting, thousands of the greatest, the funniest, the most talented and inspired, and sometimes the wierdiest men and women in America, have passed through Larry Kings life, both personal and professional, and he has a story to tell about every one of them.
Keywords: Biography